2021
DOI: 10.1111/dgd.12718
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β‐catenin signaling: Structure, assembly and endocytosis of the signalosome

Abstract: Wnt signaling is an evolutionarily conserved pathway involved in embryonic development and cell differentiation (Nusse & Clevers, 2017).In addition, it regulates many other processes, including cell growth and mitosis, adult stem cell homeostasis, and regeneration (Acebron & Niehrs, 2016;Nusse & Clevers, 2017;Reddien, 2018). Aberrant activation of the Wnt pathway lies at the basis of different types of malignancies, including colorectal, breast, and hepatic cancers.Historically, the first Wnt gene was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 199 publications
(266 reference statements)
0
36
0
Order By: Relevance
“…Indeed, mounting evidence has suggested that overexpression of Wnt/β-catenin signaling not only affects gastric cell proliferation, but also the GC relapse and metastasis by giving rise to a new cancer population of stemness-associated self-renewal cells [ 41 , 42 ]. Furthermore, the self-renewal cell activity was found to increase in HER2-positive cancer stem cells via Wnt/β-catenin signaling [ 43 ] that had also been implicated in important tumor growth processes such as cell nutrient acquisition, cell metabolism, and immune response against the tumor cells [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, mounting evidence has suggested that overexpression of Wnt/β-catenin signaling not only affects gastric cell proliferation, but also the GC relapse and metastasis by giving rise to a new cancer population of stemness-associated self-renewal cells [ 41 , 42 ]. Furthermore, the self-renewal cell activity was found to increase in HER2-positive cancer stem cells via Wnt/β-catenin signaling [ 43 ] that had also been implicated in important tumor growth processes such as cell nutrient acquisition, cell metabolism, and immune response against the tumor cells [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the activation of EGFR produces the detachment by SRC-mediated phosphorylation of the p120/E-CAD complex from the low-density lipoprotein receptor-related protein 5/6 (LRP5/6), which together with the frizzled receptors (FZD), activates the Wnt signalosome favoring the tumor cell growth [ 21 ]. Thus, HER2/EGFR activation by modulating the phosphorylation of E-CAD/βcatenin complex interferes with the sequestration of the Wnt signalosome and, in the same way, produces a reduction of E-CAD on the cell membrane and the release of sE-CAD that further may increase the EGFR signaling [ 22 , 46 ]. Moreover, serum sE-CAD/KLRG1 axis may inhibit KLRG1+ cytotoxic T-cells and NK cells function in the peripheral blood, probably suppressing their cytokine secretion and proliferation both in the periphery and in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…By Western blot Method to detect the expression of DKK1 increased, Wnt1 and β-Catenin protein in tumor tissues are reduced, and previous studies have confirmed that the Wnt1/β-catenin signaling pathway is abnormally activated in a variety of human malignant tumors, and promotes tumor invasion and metastasis. The Wnt/β-catenin signaling pathway is involved in various key cell functions, such as stem cell regeneration and organogenesis ( 25 ). In various types of malignant tumors, including breast, lung, and hematopoietic system, Wnt activation has been found, and it has been proven to help tumor recurrence ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Wnt/β-catenin signaling pathway played important roles in tumor cell proliferation, stemness, migration and chemotherapy resistance [18,33] . The protein of β-catenin nuclear translocation could induce the activation of C-myc and CyclinD1, thereby activating the Wnt/β-catenin signaling pathway [34] .…”
Section: Studies Have Shown That Tmem229 Overexpression Inhibited Cel...mentioning
confidence: 99%